POLA PEMBINAAN BACA TULIS AL-QUR’AN (BTQ) SEBAGAI UPAYA PENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN - Muhammad Hasyim Fauzan (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
Learn to read the its Al-Quran law is fardhu Ain, very ironic once when at school a lot of protege which not yet can read and write the Al-Quran better and real correct. Therefore strive the school and institute the education to push the enthusiasm of student student of so that/ to be] easy to mempejari alquran of through/ passing set of proper curriculum in aprisiasi. Through construction process which kontuitas and have ladder to can be expected can be complete of student which not yet can read and write the Al-Quran With The Applying Read To Write the Holy ( BTQ) is activity educate, teaching, guiding, and train the competitor educated / citizen learn in make-up of interest. Read To Write the Holy ( BTQ) which is in doing/conducting by alonely in local payload curriculum structure. Read To Write the Holy ( BTQ) as area curriculum is obliged to for competitor educated / citizen learn which believe in the Islam, what solely for improve the understanding and obstetrical content deed of Al-Qur'an. And Also Ability Read Al-Quran.